2003
DOI: 10.4141/p02-049
|View full text |Cite
|
Sign up to set email alerts
|

Barley response to seeding date in central Alberta

Abstract: Juskiw, P. E. and Helm, J. H. 2003. Barley response to seeding date in central Alberta. Can. J. Plant Sci. 83: 275-281. Seeding date is an important factor influencing productivity of barley (Hordeum vulgare L.). When conditions are conducive to early seeding or result in delayed seeding, producers need to know how cultivars will respond to these seeding situations. In this study, five cultivars (Abee, Harrington, Jackson, Noble and Virden) registered for western Canada were studied for 4 yr (1990 to 1993) whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
23
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 13 publications
6
23
0
Order By: Relevance
“…Similar wild oat reductions were reported in rapeseed (Brassica rapa L.) (Darwent and Smith 1985). Delayed seeding may be effective in controlling some weed species, but it normally results in lower yields for many crops, including spring wheat (Cutforth et al 1990), barley (Juskiw and Helm 2003), canaryseed (Phalaris canariensis L.) (Miller 2000), pulse crops (Gan et al 2002), and Brassica species (Brandt 1992;Kirkland and Johnson 2000).…”
supporting
confidence: 48%
“…Similar wild oat reductions were reported in rapeseed (Brassica rapa L.) (Darwent and Smith 1985). Delayed seeding may be effective in controlling some weed species, but it normally results in lower yields for many crops, including spring wheat (Cutforth et al 1990), barley (Juskiw and Helm 2003), canaryseed (Phalaris canariensis L.) (Miller 2000), pulse crops (Gan et al 2002), and Brassica species (Brandt 1992;Kirkland and Johnson 2000).…”
supporting
confidence: 48%
“…Miralles et al (2001), however, found no relationship between final leaf number and the leaf number at which the phyllochron change occurred. Jedel andHelm (1993, 1994), Juskiw et al (2001) and Juskiw and Helm (2003) have previously reported little genotypic variation in the phyllochron of two-row spring barley growing on the prairies of central Alberta, although differences in six-row spring barley were found. Using a wider genetic base in this study, we conclude that variation in phyllochron of two-row spring barley can occur and that the lack of genotypic variation observed previously is related to the narrow range of flowering dates of the two-row cultivars studied.…”
Section: Leaf Development Of the Mainstemmentioning
confidence: 99%
“…We found under both short and long days that phyllochron of two-row barley using either linear model estimates or bilinear model estimates of the early-forming leaves were positively associated with time to awn emergence. Juskiw and Helm (2003) did however, note a positive association between phyllochron and flowering date in sixrow barley.…”
Section: Leaf Development Of the Mainstemmentioning
confidence: 99%
See 2 more Smart Citations